A large-scale 19F MRI-based cell migration assay to optimize cell therapy - Bonetto, Fernando Jose (2012)
Adoptive transfer of cells for therapeutic purposes requires efficient and precise delivery to the target organ whilst preserving cell function. Therefore, therapeutically applied cells need to migrate and integrate within their target tissues after delivery, e.g. dendritic cells (DCs) need to migrate to lymph nodes to elicit an antigen-specific immune response. Previous studies have shown that inappropriate cell delivery can hinder DC migration and result in insufficient immune induction. As migration can be extremely difficult to study quantitatively in vivo, we propose an in vitro assay that reproduces key in vivo conditions to optimize cell delivery and migration in vivo. Using DC migration along a chemokine gradient, we describe here a novel 19 F MR-based, large-scale, quantitative assay to measure cell migration in a three-dimensional collagen scaffold. Unlike conventional migration assays, this set-up is amenable to both large and small cell numbers, as well as opaque tissue samples and the inclusion of chemokines or other factors. We labeled primary human DCs with a 19 F label suitable for clinical use; (0.5–15) × 106 cells in the scaffolds were imaged sequentially, and migration was assessed using two independent methods. We found no migration with larger numbers of cells, but up to 3% with less than one million cells. Hence, we show that the cell density in cell bolus injections has a decisive impact on migration, and this may explain the limited migration observed using large cell numbers in the clinic.